FACTORS INFLUENCING DELIVERY BY SKILLED BIRTH ATTENDANTS AND POSTNATAL HEALTH CHECK AMONG MOTHER IN HLAING-THARYAR TOWNSHIP, MYANMAR - Khaing, Aye Thi; Phulkerd, Sirinya; Soonthorndhada, Amara; Mon, Ayesandar; Hunchangsith, Pojjana (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Introduction: Complications during pregnancy and childbirth are the leading cause of death among women of reproductive age in Myanmar. It is generally believed by women in developing countries that pregnancy is a natural phenomenon and a part of women's reproductive functions. Problems or complications during pregnancy are also considered by such women as being natural to pregnancy. Low coverage of institutional deliveries, giving deliveries at homes without skilled provider and delays to reach to the health facilities are leading towards the vast majority of maternal deaths in Myanmar. Methods: The purpose of this study is to identify percentage of skilled birth attendant?s utilization among ever-married women (15-49 years) in Hlaing-Tharyar Township, Yangon, Myanmar. A quantitative cross-sectional survey was conducted. A total of 300 ever-married women who had delivered at least one child were selected by simple random sampling and face to face interviews were performed to them by using a pre-tested structured questionnaire. The structured questionnaire including socio-demographic background, history of last pregnancy, accessibility of health services, women?s autonomy and male involvement during pregnancy. Results: The study found that 65 percent of the sample used skilled birth attendants (SBAs) at delivery and the association between mother?s education, place of residence, parity, number of antenatal care visits, women?s autonomy and male involvement were significantly related with using skilled birth attendant at delivery and postnatal health check. About one-third (35%) were received care from non- SBAs during delivery and the postpartum period in that township. Accessibility to health services and availability of health care personnel were not significantly associated with the use of skilled birth attendants in the delivery and postpartum of the last child. Conclusions: Findings from this study highlighted that the majority of SBAs were providing reproductive healthcare services with a certain level of quality within the limited resource setting at the study area. There was a need to increase health education activities by SBAs for the pregnant and lactating mothers especially for utilization of maternal health care services. Awareness raising activities on the contraceptive method used should also be enhanced for all lactating women.